Phylogenomics illuminates the evolution of bobtail and bottletail squid (order Sepiolida) - Gustavo Sanchez (Nature Portfolio, 2021)
Sanchez, Rokhsar, and colleagues use genome skimming to generate DNA markers for phylogenomic analyses of bobtail and bottletail squid. The ancestral state of bioluminescence suggests that the Sepiolinae ancestor possessed a bilobed light organ with bacteriogenic luminescence. Also, analyses of divergence time suggest that major biogeographic events might have shaped the speciation of these animals.